On two acanthostomatid trematodes, Acanthostomum spiniceps (Looss, 1896) and A. absconditum (Looss, 1901), from African bagrid fishes - Moravec, F (Folia parasitologica, 1976)
Two species of acanthostomatid digeneans, Acanthostomum spiniceps (Looss, 1896) and A. absconditum (Looss, 1901) are redescribed on specimens obtained from Bagrus bayad and B. docmac from Egypt. Both trematode species distinctly differ from one another in the number of peribuccal spines (27--32 in A. spiniceps and 18--23 in A. absconditum) and shape and size of eggs. Therefore they cannot be considered to be conspecific. The author concludes that A. spiniceps and A. absconditum are not synonyms of A. imbutiforme (Molin, 1859), but two independent species differing both in morphology and ecology.
Keywords: Animals; ryby; Fishes; zvířata; Trematoda; Egypt